Oxidative stress homeostasis in grapevine (Vitis vinifera L.) - Carvalho, Luísa C.; Vidigal, Patrícia; Amâncio, Sara (Frontiers in Environmental Science, 2015)
Plants can maintain growth and reproductive success by sensing changes in the environment and reacting through mechanisms at molecular, cellular, physiological and developmental levels. Each stress condition prompts a unique response although some overlap between the reactions to abiotic stress (drought, heat, cold, salt or high light) and to biotic stress (pathogens) does occur. A common feature in the response to all stresses is the onset of oxidative stress, through the production of reactive oxygen species (ROS). As hydrogen peroxide and superoxide are involved in stress signaling, a tight control in ROS homeostasis requires a delicate balance of systems involved in their generation and degradation. If the plant lacks the capacity to generate scavenging potential, this can ultimately lead to death. In grapevine, antioxidant homeostasis can be considered at whole plant levels and during the development cycle. The most striking example lies in berries and their derivatives, such as wine, with nutraceutical properties associated with their antioxidant capacity. Antioxidant homeostasis is tightly regulated in leaves, assuring a positive balance between photosynthesis and respiration, explaining the tolerance of many grapevine varieties to extreme environments. In this review we will focus on antioxidant metabolites, antioxidant enzymes, transcriptional regulation and cross-talk with hormones prompted by abiotic stress conditions. We will also discuss three situations that require specific homeostasis balance: biotic stress, the oxidative burst in berries at veraison and in vitro systems. The genetic plasticity of the antioxidant homeostasis response put in evidence by the different levels of tolerance to stress presented by grapevine varieties will be addressed. The gathered information is relevant to foster varietal adaptation to impending climate changes, to assist breeders in choosing the more adapted varieties and to suitable viticulture practices.